Therapeutic Potential of Ficus benjamina: Phytochemical Identification and Investigation of Antimicrobial, Anticancer, Pro-Wound-Healing, and Anti-Inflammatory Properties - Arik Dahan; Ludmila Yarmolinsky; Arie Budovsky; Boris Khalfin; Shimon Ben-Shabat (Molecules)
Ficus benjamina is a common park tree, with previous reports of some medicinal properties. In this work, we identified and explored phytochemicals from F. benjamina for potential antimicrobial, pro-wound-healing, anti-inflammatory, and effect on cancer cell lines’ proliferation, both experimentally and bioinformatically. Gas chromatography/mass spectrometry (GC/MS) analysis was performed to identify the volatile compounds. The nonvolatile active components of the extract were identified by HPLC and LC-ESI-MS. We found that some drug-resistant microorganisms (Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, Serratia marcescens, and Salmonella enteritidis) were inhibited by the extract, the 80% fraction, and all the identified flavonoids except quercetin 3-O-rutinoside. Furthermore, the extract and above-mentioned compound also inhibited the growth of biofilm-producing bacterium. The extract and 80% fraction were very potent (p < 0.001) at inducing death of MCF7 and U87 cancer cell cultures and were more effective in that than the chemotherapeutic agent doxorubicin which served as a positive control. Additionally, the extract of F. benjamina, the 80% fraction, and selected phytochemicals had pronounced pro-wound-healing properties. Finally, the extracts, the 80% fraction, caffeic acid, kaempferol 3-O-rutinoside, and kaempferol 3-O-robinobioside significantly inhibited the secretion of pro-inflammatory cytokines, IL-6 and IL-8 (p < 0.001). In conclusion, this comprehensive research revealed convincing and promising indications of significant therapeutic potential of a F. benjamina extract and its active phytochemicals.